Combinatorial Optimization : Algorithms and complexity - Papadimitriou, Christos H.; Steiglitz, Kenneth (New York Dover Publications, Inc., 1998)
This book includes a novel algorithmic exposition of the simplex method and also discusses the Soviet ellipsoid algorithm for linear programming; efficient algorithms for network flow, matching, spanning trees, and matroids; the theory of NP-complete problems; approximation algorithms, local search heuristics for NP-complete problems, more.
Includes bibliographical references and index
Keywords: Công nghệ thông tin